Oral Cavity Disorders Among Patients With Parkinson’S Disease - Case Reports - Łanowy, Patrycja; Bichalski, Miłosz; Mocny-Pachońska, Katarzyna; Mocny-Pachoński, Marek; Tanasiewicz, Marta (Journal of Education, Health and Sport, 2019)
Parkinson's disease (PD) is a progressive, neurodegenerative ailment, caused by the loss of dopaminergic neurons in the specific area of a brain. Motor disability which is a symptom of PD, make maintaining the proper hygiene in the mouth difficult. Despite motor disorders, also cognitive dysfunctions can have a negative impact on the oral health of the patient, due to the lack of interest in the condition of the patient's oral cavity. Non-motor symptoms and even those associated with the oral cavity may be an indication for proper and early diagnosis of the patient. Disorders which occurs in the oral cavity during the sickness, are often neglected by patients and their caregivers. The role of the dentist in this situation is to make patients and their environment aware of the importance of the oral cavity - especially, due to the fact that newest studies suggest the association between ongoing systemic inflammation in the body, including periodontitis, and the development and progression of Parkinson's disease.